Implementation of stabilisation measures by the National Police in the context of creating a secure environment in the de-occupied and frontline territories - K. L. Buhaichuk (Law and Safety)
A comprehensive analysis of the bodies and units of the National Police of Ukraine activities in the de-occupied territories and in the territories close to the combat zone is carried out. It is emphasised that the exercise of police powers in such territories is characterised by very rapid dynamics due to the constant change of the operational situation, increased physical and psychological stress.